Influence of limb temperature on cutaneous silent periods - Kofler, Markus; Valls-Solé, Josep; Vasko, Peter; Boček, Václav; Štetkárová, Ivana (Clinical neurophysiology, 2014)
OBJECTIVE: The cutaneous silent period (CSP) is a spinal inhibitory reflex mediated by small-diameter afferents (A-delta fibers) and large-diameter efferents (alpha motoneurons). The effect of limb temperature on CSPs has so far not been assessed. METHODS: In 27 healthy volunteers (11 males; age 22-58 years) we recorded median nerve motor and sensory action potentials, median nerve F-wave and CSPs induced by noxious digit II stimulation in thenar muscles in a baseline condition at room temperature, and after randomly submersing the forearm in 42 °C warm or 15 °C cold water for 20 min each. RESULTS: In cold limbs, distal and proximal motor and sensory latencies as well as F-wave latencies were prolonged. Motor and sensory nerve conduction velocities were reduced. Compound motor and sensory nerve action potential amplitudes did not differ significantly from baseline. CSP onset and end latencies were more delayed than distal and proximal median nerve motor and sensory latencies, whereas CSP duration was not affected. In warm limbs, opposite but smaller changes were seen in nerve conduction studies and CSPs. CONCLUSION: The observed CSP shift "en bloc" towards longer latencies without affecting CSP duration during limb cooling concurs with slower conduction velocity in both afferent and efferent fibers. Disparate conduction slowing in afferents and efferents, however, suggests that nociceptive EMG suppression is mediated by fibers of different size in the afferent than in the efferent arm, indirectly supporting the contribution of A-delta fibers as the main afferent input. SIGNIFICANCE: Limb temperature should be taken into account when testing CSPs in the clinical setting, as different limb temperatures affect CSP latencies more than large-diameter fiber conduction function.
Keywords: dospělí; Motor Neurons; Physiology; Female; Cutaneous silent period; tělesná teplota; Nerve conduction; teplota; Adult; mladý dospělý; Action Potentials; ženské pohlaví; Reflex; Sensory Thresholds; Extremities; lidé; nervové receptory; senzorické prahy; Nerve Fibers, Myelinated; Neural Conduction; kůže; nervové vedení; Median Nerve; Sensory Receptor Cells; Temperature; Male; Body Temperature; A-delta fiber; Skin; Young Adult; motorické neurony; končetiny; reflex; lidé středního věku; mužské pohlaví; Spinal reflex; nervová vlákna myelinizovaná; Middle Aged; nervus medianus; akční potenciály; Humans